Study on Decomposition and Transformation of Calcite-1 by Shearing at High Pressure - Furuichi, Hiroshi (Recent Trends in Chemical and Material Sciences Vol. 5, 2022)
Transmission X-ray diffraction patterns were taken on imaging plates from calcite-1 slowly sheared at high pressure up to 16 GPa parallel to (101) plane and in the [2-1-1] direction at room temperature. They showed 22 broad diffused rings. Judging from the appearance of the rings, we may say that the formed substances are in an amorphous state. The patterns revealed that most of the rings do not correspond to calcite-1, but to high-pressure substances except graphite2H, CaO and CaC2. They were thought to have formed through decomposition and transformation to its polymorphism. They remain at atmospheric pressure. Although the results mentioned above seem to be contrary to the common knowledge among scientists, phenomena that support the results are mentioned in the text. Severe discontinuous dry rubbing decomposes a compound to simple substances and compounds constituting of the elements of the original compound. Calcite-I sheared at high pressure not only transformed to its polymorphism but also decomposed to compounds and simple substances.